Pengembangan Bahan Ajar Menulis Puisi dengan Perpaduan Model Demonstrasi dan Teknik Beriur Kata Kelas VIII SMP - Gigih Yudha Pratama; Jafar Haruna; M. Siddik (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
The purpose of this study (1) to test the development of poetry writing teaching materials planning with a combination of demonstration models and class VIII word giving techniques in junior high school; (2) test the feasibility of the design of poetry writing teaching materials with a combination of demonstration models and class VIII word grammar techniques; and (3) testing the effectiveness of developing poetry writing teaching materials with a combination of demonstration models and class VIII word syllabic techniques. This development research refers to the 10 stages of Borg & Gall which are simplified into 3 stages, namely information gathering, product manufacturing planning, and product development. The results showed that the development of planning poetry writing teaching materials with a combination of demonstration models and class VIII word syllabary techniques has 14 important parts. The average score of assessment and validation by media experts, material experts, and Indonesian language teachers was obtained 4.43, this value means teaching poetry writing material with a combination of demonstration models and class VIII word giving techniques is very suitable to be used as an independent teaching material for students Class VIII Middle School. The results of the trial evaluation and validation of each aspect obtained an average score of 4.58, this value means the teaching material of writing poetry with a combination of demonstration models and class VIII wordbearing techniques is very effective according to the responses of students of class VIII SMP.